Caracterização dos professores de Educação Física que trabalham com esporte extraclasse: motivações, trajetórias, saberes e identidades - Andrade, Danielle Muller de (2011)
Although the current context of education depicts a scenario of disdain, disbelief and devaluation of the teaching profession, are in schools motivated and committed professionals, professionals who use resources, seek alternatives and engage with the same. These professionals often go unnoticed and appear to non exist in the public schools. To contribute to greater reflection on teacher motivation, a topic widely discussed in education, this study aims to trace the characterization of physical education teachers who work with extracurricular sports in College Hall Pelotense, the from their motivations, their careers, their knowledge and identities. Characterized as a qualitative and descriptive study,like a study case. For the data collection instrument were used a semi-structured interviews which were transcribed later to be analyzed and discussed. The subjects in this study were six teachers involved in extracurricular sports activities at the school. The study results point to a scenario where teachers, mostly men and ex athletes, trained in ESEF / UFPel, are at different stages of professional development, with different expectations about the future. They are motivated to work, though not fully satisfied. The feelings of satisfaction concerning the development of students, since the dissatisfaction is related to work conditions and low wages. The knowledge used in their practices are related to their trajectories, particularly, their experiences with the sport. They point out that professional development is hampered by the lack of professional training policies. The training materials are from the personal commitment of teachers. Recognize themselves and are recognized by the wider community as competent professionals. Such recognition promotes increased self-esteem and influence in the motivation of teachers